Parishin A ameliorates cognitive decline by promoting PS1 autophagy in Alzheimer’s disease - Guo, Song; Yi, Lilin; Luo, Man; Dong, Zhifang; Du, Yehong (Frontiers in Aging Neuroscience, 2025)
IntroductionAlzheimer’s disease (AD) is a common neurodegenerative disease in the elderly. Its pathological features include: A lot of misfolding and abnormal aggregation of amyloid protein (Aβ); Autophagy disorder, oxidative stress, neuroinflammation, abnormal phosphorylated tau protein and synaptic dysfunction. Modern pharmacological studies have found that Paisinhin A (PA) has beneficial effects on the prevention and treatment of central nervous system diseases. This study aims to explore the role and mechanism of PA in AD through autophagy pathway, and lay a scientific foundation for the development of clinical prevention and treatment strategies for AD.MethodsN2AAPP cells were treated with different concentrations of PA. Cell viability was detected by CCK-8 method. Western blotting detected the expression levels of proteins related to amyloid production, autophagy pathway, and phosphorylated Tau expression levels. Autophagy flow was detected by transfecting Lc3 double fluorescent plasmid. After Aβ was injected into the hippocampus of WT mice and PA was injected intraperitoneally, the learning and memory ability of WT mice were tested by new object recognition, y maze and water maze. The oxidative stress level was detected by the kit. The levels of inflammatory factors were detected by RT-qpcr.ResultsThe viability of N2AAPP cells was not affected at different concentrations of PA, but PS1 was significantly decreased at 40μM. PA can obviously improve the accumulation of autophagy in AD, and to some extent save the autophagy inhibition of CQ. Behavioral studies have shown that PA can also improve learning and memory impairments caused by Aβ injections. In addition, in vivo experiments, PA can also improve oxidative stress levels, inflammation levels and salvage dysfunctions of synapses. PA also reduces the levels of total and phosphorylated Tau in N2ATau.DiscussionOur study provides the first evidence that PA improves learning and memory in Aβ-induced AD mice. This effect appears to be mediated by PA by promoting autophagy and reducing oxidative stress. It was also found that PA may have a role in regulating inflammation, improving abnormally phosphorylated tau, and salvaging damaged synaptic function, providing valuable insights into potential applications in the treatment and prevention of AD.